10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
BACKGROUND: The Latarjet procedure is widely used for recurrent anterior shoulder instability with glenoid bone loss. Arthroscopic techniques are increasing; however, there is limited evidence for mid- to long-term outcomes. PURPOSE: To evaluate clinical outcomes, recurrence rates, and quality of life at a minimum of 5 years' follow-up after undergoing the arthroscopic Latarjet procedure. STUDY DESIGN: Cohort study; Level of evidence, 3. METHODS: Patients who underwent the arthroscopic Latarjet procedure using double-screw fixation at Oslo University Hospital between 2014 and 2019 were prospectively registered. Descriptive data and Western Ontario Shoulder Instability Index (WOSI) scores were recorded preoperatively and at 1 and 5 years postoperatively. At 5 years, complications and health-related quality of life (HRQoL; EQ-5D-5L) were assessed. RESULTS: Of 107 patients who underwent the arthroscopic Latarjet procedure, 93 cases met the inclusion criteria. After loss to follow-up, 85 cases were included. The median follow-up time was 5.2 years (range, 5.1-9.4 years). The median age at surgery was 27.8 years (range, 15.6-49.8 years), and 78 of 85 (92%) cases were male. Of the 85 cases, 56 (66%) had >10 dislocations before surgery, and 36 (42%) were revision procedures. At the 5-year follow-up, 2 of 85 patients experienced recurrent dislocations, and 8 of 85 reported subluxations. The median WOSI score improved significantly from 51% (IQR, 29.1%-62.4%) preoperatively to 79% (IQR, 62.9%-91.4%) at 5 years (P < .001). The median WOSI score at 1 year was 80% (IQR, 67%-88.4%), with no significant difference between the 1-year and 5-year scores (P = .69). The mean EQ-5D-5L index scores at 5 years were 0.889 ± 0.169 compared to 0.896 ± 0.177 for general population norms, with no significant difference (P = .77). Overall, 87% of patients reported satisfaction with the surgical outcome. Ten patients underwent reoperation due to complications. CONCLUSION: At a minimum 5-year follow-up, the arthroscopic Latarjet procedure resulted in significant improvement in WOSI score, low rates of recurrent dislocation, and high patient satisfaction. The WOSI score remained stable over 1 to 5 years. HRQoL, assessed using the EQ-5D-5L index, was comparable to age- and sex-matched general population norms at 5 years, supporting a satisfactory long-term impact on HRQoL.